The understanding of the economy in Max Weber: fundamentals of its approach in economic and business thinking (GEON Journal (Management, Organizations and Business), 2018)
This document is the result of a literature review and an effort to organize the ideas expressed by several thinkers of a great sociologist and economist such as Max Weber, in order to open a debate about economic thought. To this end, ideas were taken from various authors and key texts to understand the traced themes, which are combined with ideas for the final result.
Keywords: Economics; business thinking; economic thinking; Max Weber